Skill sheets : an integrated approach to research, study and management - van Tulder, Rob, 1956- (Amsterdam : Pearson, 2018)
In today's society, there is a growing need for so-called 21st century skills, which can range from sophisticated analytical skills and practical social skills to dealing with great complexity and uncertainty. Whether you are a student, a manager or a researcher, vital skills are interconnected and require real-time application. Skill development is an integrated and lifelong accumulative process that requires a solid understanding of the type of motivation and attitude needed to make the experience rewarding, intriguing and... fun. This book consists of a collection of one hundred Skill Sheets that explain the basic principles of a holistic approach to skill development. The sheets are organised around a set of seven comprehensive skills: research, study and self-management, reading, listening, writing, presenting, and team and project management. This upgraded and extended third edition brings the Skill Sheets to the next level by introducing an additional challenge: Education of the Heart, or: how to combine 'head' (logic), 'heart' (passion and motivation) and 'hands' (practice) into the skill development equation. Over the past twenty years, students and managers as well as tutors and professors around the world have found Skill Sheets to be an eminently practical reference book, valid throughout their entire education and career. The formula has been tested, improved and updated at a variety of universities, including the Erasmus University Rotterdam, one of Europe's leading educational institutions.